Turn the pain and affliction into thinking about the beauty: Teaching young women as a form of saving one’s life in the light of memories from the all-female German Nazi concentration camp - FKL Ravensbrück of Wanda Półtawska, Urszula Wińska and Karolina Lanckorońska - Filipowicz, Bogusława (Kwartalnik Naukowy Fides et Ratio, 2021)
Abstract: The article reflects on the importance of opposing Polish women - prisoners of the German Nazi concentration camp FKL Ravensbrück - to the practices of the German authorities (guards and medical staff of this camp) used against prisoners. One of the forms of opposing the totalitarianism of the Third Reich was secret teaching. At FKL Ravensbrück, female teachers taught fellow prisoners - “the rabbits”. This term was used to describe the women who underwent medical experiments in the camp: 74 Polish women and 12 women of other nationalities. Professor Karolina Lanckorońska found herself in the camp’s conspiratorial teaching staff. The source base for the analysis are the war memories of female prisoners, including Dr. Wanda Półtawska and Dr. Urszula Wińska. The summary shows the issue of the protection of values by people subjected - against their will - to life in extreme conditions.